The Newly Identified T Helper 22 Cells Lodge in Leukemia - Gholamreza Azizi; Mohsen Rastegar Pouyani; Shadi Sadat Navabi; Reza Yazdani; Fatemeh Kiaee; Abbas Mirshafiey (International Journal of Hematology-Oncology and Stem Cell Research, 2015)
Leukemia is a hematological tumor in which the malignant myeloid or lymphoid subsets play a pivotal role. Newly identified T helper cell 22 (Th22) is a subset of CD4(+) T cells with distinguished gene expression, function and specific properties apart from other known CD4(+) T cell subsets.Th22 cells are characterized by production of a distinct profile of effector cytokines, including interleukin (IL)-22, IL-13, and tumor necrosis factor-α (TNF-α). The levels of Th22 and cytokine IL-22 are increased and positively related to inflammatory and autoimmune disorders. Recently, several studies have reported the changes in frequency and function of Th22 in acute leukemic disorders as AML and ALL. This review discusses the role of Th22 and its cytokine IL-22 in the immunopathogenesis of leukemic disease.